THU0331 Increased Incidence of Tuberculosis Among Systemic Lupus Erythematosus Patients – Should Tuberculosis Screening at Diagnosis be the Next Step?. (9th June 2015) - Gherghe, A.M.; Matei, A.; Györfi, H.; Soare, A.; Dobrota, R.; Sasu, M.; Macovei, L.; Ancuta, I.; Ciofu, C.; Milicescu, M.; Bojinca, M.; Stoica, V.; et al.
Abstract : Background: World Health Organization (WHO) declared tuberculosis (TB) the most common infectious disease in the world. TB has a higher incidence among patients with systemic rheumatic diseases than in the general population; in such patients, it frequently presents as extrapulmonary or disseminated disease. According to WHO surveillance reports, although steadily decreasing during the last years, the incidence of TB in Romania in 2005-2014 was by far the highest among all EU countries. Objectives: To assess the characteristics and risk factors of active TB infection in a cohort of patients with systemic lupus erythematosus (SLE). Methods: Data of all SLE patients followed up in our clinic in 2005 – 2014 were retrospectively analyzed. Clinical and demographic characteristics and treatment before diagnosis of TB were recorded. The incidence of active TB infection was compared to data from the general population. Univariable logistic regression was used to assess the influence of various factors on the risk of developing TB. Results: Four hundred SLE patients were evaluated in our clinic during the 10-year interval; of them, 18 cases of active TB per 4291 patient-years (time of exposure, PY) were identified, accounting for an incidence of 419.5/100.000 PY, which is 4.43 times the incidence of TB in our region in the period 2005-2014. Ten of the 18 cases had extrapulmonary or disseminated TB; delayed diagnosis and more severe forms were observed in them. Two patients repeatedly had active TB infection after 2, respectively 3 years from the first TB diagnosis. High-dose glucocorticoids (hd-GC) and cyclophosphamide (CYC) treatment were significantly associated with TB: OR (95% CI) 9.6 (1.2-77.5), p=0.03 for hd-GC and 3.3 (1.2-9.1), p=0.02 for CYC. Fever was the most important red-flag for the diagnosis of TB, OR (95% CI) 73.1 (15.2-352.7), p<0.001. Other frequent manifestations were weight loss and cough. No association was found between TB and age, disease duration or socio-economic status. Conclusions: We found an increased incidence of active TB infection with a majority of extrapulmonary TB in a large cohort of Romanian SLE patients. Cyclophosphamide treatment and high daily dose of glucocorticoids before the diagnosis of TB were important determinants for the increased risk of TB in SLE patients. These results suggest that in a country with high TB burden, TB screening and treatment of latent TB would be useful before initiation of immunosuppressive treatment. Disclosure of Interest: None declared